Spectrophotometric analysis of total ascorbic acid content in fruits and vegetables - Kapur, Ajla; Hasković, Alisa; Čopra-Janićijević, Amira; Klepo, Lejla; Topčagić, Anela; Tahirović, Ismet; Sofić, Emin (Bulletin of Chemists and Technologists of Bosnia and Herzegovina, 2012)
Total ascorbic acid (ascorbic acid + dehydroascorbic acid) has been determined in twenty-one different samples of fruits and vegetables by spectrophotometric method. This method is based on the oxidation ascorbic acid to dehydroascorbic acid by bromine water in the presence of acetic acid. After coupling with 2,4-dinitrophenylhydrazine (DNPH) a red complex was produced and absorbance of that complex was spectrophotometrically measured at 521 nm. A linear concentration range for standard solutions of ascorbic acid was obtained up to 10 μg mL-1, with a correlation coefficient of 0.9929. The contents of ascorbic acid were found between 9 and 49 mg/100 g of fresh fruits, also 3 and 90 mg/100 g of fresh vegetables. The interferences of glucose, fructose and sucrose were also investigated. The limit of detection of ascorbic acid was found to be 0.01 μg mL-1 (3σ from 10 measurements of ascorbic acid concentration of 3 μg mL-1), and limit of quantification of ascorbic acid was 0.017 μg mL-1. A relative standard deviation was 2.4% (n = 10, c = 7 μg mL-1). The content of total ascorbic acid in twenty-one different samples of fruits and vegetables was compared with results of spectrofluorimetric method and literature values.